FINANCIAL STATEMENTS FOR THE ECONOMY. - Friend, Irwin (The Accounting Review, 1949)
Abstract In recent years social accounting or the construction of financial statements for the entire economy has become increasingly important in the thinking of the general public and in the formulation of policies by Government officials and businessmen. The over-all financial statements now in use or potentially of future importance are based on three types of accounts completely familiar to all business accountants, namely, income accounts, balance sheets and a derived sources and uses of funds analysis. The last of course, shows the origin and disposition of funds for capital purposes as well as on current account. Such financial statements are now recognized as essential in the appraisal of economic activity and to the analysis of the significant interrelationships within the economy, however, they must be supplemented by several other types of related data, notably by deflated figures expressing economic activity in real as well as dollar terms and by what might be called anticipation. The latter category includes new and unfilled orders and budget data, particularly planned capital expenditures. Anticipation statistics, which like the historical figures are also based on accounting data, are of particular importance since the interest in the past and present is largely dependent on the insight it gives one into the future.